Pathway to diagnosis and burden of illness in mucopolysaccharidosis type VII – a European caregiver survey - Alexandra Morrison; Esmee Oussoren; Tabea Friedel; Jordi Cruz; Nalan Yilmaz (Orphanet Journal of Rare Diseases, 2019)
Abstract Background Mucopolysaccharidosis type VII (Sly disease, MPS VII), is an ultra-rare, multi-symptom disease with variable clinical presentations which can present challenges with diagnosis, management and care. We believe this survey is the first to explore the patient experience through direct questioning of the caregivers of 13 individuals with MPS VII. Methods This European survey, using a specifically designed questionnaire, was conducted in order to describe the pathway to diagnosis and the burden of illness of MPS VII. Information on early symptoms, clinicians seen, and current symptoms was collected. Questions on the caregivers’ ability to work and the use and availability of health, social and educational support were included. Results Caregivers of 13 patients from Germany, Spain, The Netherlands and Turkey responded to the survey. Five patients with non-immune hydrops fetalis (NIHF) were diagnosed with MPS VII at a mean age of 1.9 years (median 0.3 years, range 0.2 to 6 years). Those without NIHF (n = 7) were diagnosed at a mean age of 6.1 years (median 6.0 years, range 1.9 to 14 years). The symptoms most likely to raise a suspicion of MPS VII, excluding NIHF, did not appear until a median age of at least three years. Over one half of patients required assistance with daily living and mobility. Reduction of the working hours of caregivers was often necessary (46.2% reduced hours, 30.8% stopped working). Patients attended frequent medical appointments (12.7/year), over 80% had surgery and 30% had been hospitalised for respiratory issues. While support for learning and behavioural needs was generally available, support for mobility was not available to 50% of patients. Half of the respondents (6/12) said they were not offered genetic counselling. Conclusions For children that do not present with NIHF, diagnosis can take several years as early symptoms can be non-specific and mistaken for other conditions. Increased awareness of the early signs of disease and more information for parents/caregivers at diagnosis are needed. MPS VII poses significant burden to patients, caregivers, healthcare, social and educational services. Access to information and support varies across Europe and the availability of genetic counselling is limited in some countries.